Compliance with treatment groups: an interdisciplinary strategy for assistance to HIV/AIDS patients - Gil, K. A. S.; Lima, D. L. P.; Pegorete, T. R.; Cavalcanti, P. P. (Scientific Electronic Archives, 2017)
The objective of this research was to identify the benefits of adherence group to HIV / AIDS and evaluate the work of an interdisciplinary team of health. It is a descriptive and exploratory study of qualitative approach, with 5 volunteers and 3 professionals who provide care in the Specialized Care Service (SAE) of Sinop/MT. Data were collected through semi-structured and recorded interviews. The answers were transcribed and analyzed in categories. The results showed that the participation of people living with HIV / AIDS in the adherence group offered a significant help for their adherence to treatment and improved quality of life, and the work of professionals in the group contributed effectively to patient compliance treatment as an alternative therapy. The group also provided the user of the Unified Health System (SUS) assistance of paid way. Thus, it was found that the use of group activities may be a possibility of nursing care, constituting a valuable space for the patient to find the necessary support to adhere to the treatment.